The effects of ILFN-exposure on voice acoustic parameters of commercial cabin crewmembers - Mendes, Ana (2016)
Background: Long-term exposure to infrasound and low frequency noise (ILFN <500 Hz, including infrasound) can lead to the development of vibroacoustic disease (VAD). VAD is a systemic pathology characterized by the abnormal growth of extracellular matrices in the absence of inflammatory processes, namely of collagen and elastin, both of which are abundant in the basement membrane zone of the vocal folds. ILFN-exposed workers include pilots, cabin crewmembers, restaurant workers, ship machinists and, in previous studies, even though they did not present vocal symptoms, ILFN-exposed workers had significant different voice acoustic patterns (perturbation and temporal measures) when compared with normative population. Study Aims: The present study investigates the effects of age and years of occupational ILFN-exposure on voice acoustic parameters of 37 cabin crewmembers: 12 males and 25 females. Specifically, the goals of this study are to: 1) Verify if acoustic parameters change over the age and years of ILFN-exposure and 2) Determine if there is any interaction between age and years of ILFNexposure on voice acoustic parameters of crewmembers. Materials and Methods: Spoken phonatory tasks were recorded with a C420III PP AKG head-worn microphone and a DA-P1 Tascam DAT. Acoustic analyses were performed using KayPENTAX Computer Speech Lab and Multi-Dimensional Voice Program. Acoustic parameters included speaking fundamental frequency, perturbation measures (jitter, shimmer and harmonicto- noise ratio), temporal measures (maximum phonation time and s/z ratio) and voice tremor frequency. Results: One-way ANOVA analysis revealed that as the number of ILFN-exposure years increased male cabin crewmembers presented significant different shimmer values of /i/ as well as tremor frequency of /u/. Females presented significantly different jitter % of /i, a, O/ (p <0.05). Lastly, Two-way ANOVA analysis revealed that for females, there was a significant interaction between age and occupational ILFN-exposure for voice acoustic parameters, namely for jitter’s mean for /a, O/ and shimmer’s (%) mean for /a, i/ (p <0.05). Discussion and Conclusion: These perturbation measure patterns may be indicative of histological changes within the vocal folds as a result of ILFN-exposure. The results of this study suggest that voice acoustic analysis may be an important tool for confirming ILFN-induced health effects.